PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATIONN TERHADAP KEMAMPUAN PEMAHAMAN KONSEP PESERTA DIDIK KELAS VII SMP PEMBANGUNAN LABORATORIUM UNP - MUHAMMAD IQBAL (Jurnal Edukasi dan Penelitian Matematika, 2020)
Purposes this study is analyze and describe theQability to understand theQconcept of learners who learn to use cooperative models Group Investigation type is better than the ability to understand the concepts of studentsQwho learn with conventionalQlearning. ThisQtype of studyQis a quasiQexperimental and studyQdesign is Posttest-only nonequivalentQcontrol groupQdesign. The studyQpopulation is students gradeQVII of the Pembangunan Laboratorium UNP JuniorQHigh SchoolQin the secondQhalf of the 2019/2020 Academic Year. Sampling of this study is conducted usingQpurposive samplingQtechnique. The studyQsample is classQVII. A as an experimentalQclass and class VII. D as a controlQclass. This studyQinstrument is a testQof understandingQmathematical concepts. HypothesisQtesting of this study use t-test. The result obtained by P-value is 0.033. Thus the P-value < real level, a = 0,05. its meansQthat H0 isQrejected and H1 isQaccepted. This means that the cooperative learning type group invesrigation modelQhas a significantQeffect onQthe understandingQof the concept of the students grade VII at Pembangunan Laboratorium UNP Junior HighQSchool in the secondQhalf of the 2019/2020 Academic Year Keywords — Uunderstandinggof mathernatical conccepts, group investigation model, conventional learning